The Forward Premium Puzzle only emerges gradually - Kerstin Bernoth; Jürgen von Hagen; Casper G. de Vries (Tinbergen Institute, 2007)
The forward premium puzzle (FPP) is the negative correlation between the forward premium and the realized exchange rate return at maturities of a month and beyond. Some recent evidence shows that at maturities of multiple years and at the highest intra day frequency the correlation is positive and close to one. This paper contributes by using futures data instead of forwards to complete the maturity spectrum at the (multi-) day level. We find that the correlation only slowly turns negative as the number of days to maturity is increased to the monthly level. The typical shape of the premium correlation with regard to the forward maturity length appears to be V-shaped.
Keywords: F31; F37; G13; 330; exchange rates; market efficiency; forward premium puzzle; uncovered interest parity; futures rates; Währungsderivat; Wechselkurs; Währungsrisiko; Fälligkeit; Effizienzmarkthypothese